An investigation of the impact of facial affect recognition impairments in moderate to severe TBI on fatigue, depression, and quality of life. (4th May 2017) - Genova, Helen M.; Genualdi, Andrew; Goverover, Yael; Chiaravalloti, Nancy D.; Marino, Cherylynn; Lengenfelder, Jeannie
ABSTRACT: Individuals with moderate to severe traumatic brain injury (TBI) have been shown to experience significant problems in facial affect recognition (FAR). However, it is not known how these impairments relate to overall functioning and quality of life (QoL) following TBI. The aim of the current study was to test the hypothesis that worse performance on an FAR task would be associated with reduced QoL (related to social and emotional functioning), worse mood, and increased fatigue. Forty-seven individuals with TBI and 27 healthy controls (HCs) completed the facial emotion identification task (FEIT), as well as questionnaires assessing social and emotional QoL, mood, and fatigue. The TBI group performed significantly worse than HCs on the FEIT. A significant relationship between FAR and fatigue and QoL related to social and emotional functioning was documented, but in an unexpected direction: individuals who performed better on the FEIT reported poorer QoL and greater fatigue. Individuals who have better FAR may require increased effort to perform this task, and thus experience greater fatigue and poorer social and emotional QoL.